2020
DOI: 10.1056/nejmoa2020283
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Association Study of Severe Covid-19 with Respiratory Failure

Abstract: BACKGROUNDThere is considerable variation in disease behavior among patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes coronavirus disease 2019 . Genomewide association analysis may allow for the identification of potential genetic factors involved in the development of Covid-19. METHODSWe conducted a genomewide association study involving 1980 patients with Covid-19 and severe disease (defined as respiratory failure) at seven hospitals in the Italian and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
1,491
18
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,727 publications
(1,705 citation statements)
references
References 42 publications
80
1,491
18
27
Order By: Relevance
“…With this in mind, even though the collected knowledge is still limited to few studies, some susceptibility markers other than HLA have been proposed for Covid-19. An association with ABO blood antigens has been observed in a cohort of Chinese patients, with the type A and 0 being respectively at highest and lowest risk to be infected, as previously been reported for other viral infections [36,37]. Genetic polymorphisms of key genes of the virus entry machinery (Ace2, Tmprss2, CtsB, and CtsL) or of the in ammatory/immune response (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…With this in mind, even though the collected knowledge is still limited to few studies, some susceptibility markers other than HLA have been proposed for Covid-19. An association with ABO blood antigens has been observed in a cohort of Chinese patients, with the type A and 0 being respectively at highest and lowest risk to be infected, as previously been reported for other viral infections [36,37]. Genetic polymorphisms of key genes of the virus entry machinery (Ace2, Tmprss2, CtsB, and CtsL) or of the in ammatory/immune response (e.g.…”
Section: Discussionsupporting
confidence: 66%
“…For rs657152, the overall frequency of the protective allele C was 0.5468 (222/406) in our data, with the lowest rate found in the critical group (AF = 0.382, 13/34, Fisher's exact test P = 0.04896). For rs11385942, the risk allele GA was not detected in any patient in our study, as this variant was rare in Chinese people 27 (Supplementary Table 4.4), consistent with previously reported global distribution 26 . Quantitative trait locus (QTL) analysis has been widely applied to infer the contribution of genetic variations to complex phenotypes 28 .…”
Section: Genomic Architecture Of Covid-19 Patientssupporting
confidence: 91%
“…Additionally, PTGIS possesses anti-in ammatory properties by modulating the expression of IL-1, IL-6, IL-10, which may be associated with the COVID-19 severity 25 . We also assessed two loci, rs657152 at locus 9q34.2 and rs11385942 at locus 3p21.31, which have been found to be associated with COVID-19 patients with severe respiratory failure in Spanish and Italian populations 26 . For rs657152, the overall frequency of the protective allele C was 0.5468 (222/406) in our data, with the lowest rate found in the critical group (AF = 0.382, 13/34, Fisher's exact test P = 0.04896).…”
Section: Genomic Architecture Of Covid-19 Patientsmentioning
confidence: 99%
“…rs11385942 may act trough the regulation of the memory lymphoid cell migration Expression pro les generated by scRNA-seq can be overlaid with genome-wide association studies (GWASs) to pinpoint speci c cell types and identify potential cellular and molecular mechanisms explaining the described genetic associations [28]. In addition to the ABO group locus, a recent study found that another genomic locus is associated with the development of severe forms of COVID-19 [23].…”
Section: Covid-19 Affects Blood and Lung Lymphocyte Compartments In Amentioning
confidence: 99%
“…Unfortunately, none of the past studies analyzed the immune regulatory properties of myeloid cells at functional level. A speci c genetic locus including immune related genes (such as C-X-C motif chemokine receptor 6 -CXCR6), was found to be associated with worse prognosis in COVID-19 patients [23]. Other studies exclusively performed on broncho-alveolar lavage uids (BAL), elucidated the sustained interplay between macrophages releasing in ammatory cytokines and lung epithelial cells in more severe COVID-19 disease stages [21], whereas pointed out highly clonally expanded CD8 + T cells in moderate patients [22].…”
Section: Introductionmentioning
confidence: 99%